2011
DOI: 10.1109/tip.2010.2064327
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Detection of Additive Watermarking in the DWT-Domain

Abstract: Abstract-This article aims at lightweight, blind detection of additive spread-spectrum watermarks in the DWT domain. We focus on two host signal noise models and two types of hypothesis tests for watermark detection. As a crucial point of our work we take a closer look at the computational requirements of watermark detectors. This involves the computation of the detection response, parameter estimation and threshold selection. We show that by switching to approximate host signal parameter estimates or even fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…Our own experiments showed that GGD and Cauchy model parameters are hard to reliably estimate on heavily quantized data (e.g. H.264 4 × 4 DCT residuals) and that the corresponding LRT detectors do not achieve optimal performance even employing ML estimates [10].…”
Section: Application Considerationsmentioning
confidence: 99%
“…Our own experiments showed that GGD and Cauchy model parameters are hard to reliably estimate on heavily quantized data (e.g. H.264 4 × 4 DCT residuals) and that the corresponding LRT detectors do not achieve optimal performance even employing ML estimates [10].…”
Section: Application Considerationsmentioning
confidence: 99%
“…Without loss of generality, y and w * are assumed to be vectors of length N . In the literature [18,21,22,33], it is well established that the detection response ρ follows a Chi-square distribution with one degree of freedom (χ 2 1 ) under hypothesis H 0 , whereas under hypothesis H 1 , it follows a Non-Central Chi-square distribution with one degree of freedom and non-centrality parameter (χ 2 1, ), as shown in Fig. 4.…”
Section: Watermark Embedding and Detectionmentioning
confidence: 99%
“…After inspecting the Rao detector structure, there is only one parameter (i.e., the shape parameter β) to be estimated directly from the watermarked coefficients. However, as mentioned in [22,33], the detector presented by (11) is asymptotically optimal, which means that the host data needs to be adequately large. In this section, intensive experiments have been conducted to evaluate the performance of the proposed watermarking system on a set of test images.…”
Section: Watermark Embedding and Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical analysis of the properties of correlator detector is used to derive an optimal fused correlator. Detection [7] based on additive watermarking in DWT domain is considered using spread spectrum technique. For watermark detection, two signal models and two hypothesis tests are considered.…”
Section: Introductionmentioning
confidence: 99%